Răspuns :
Răspuns:
b)X=1/3
Y=-2/3
f)x=-4
Y=6
Explicație pas cu pas:
B)4x-2y=0
X-y=-1 |x2
4x-2y=0
2x-2y=-2
(adunam)
6x=-2
X=-2/6
X=1/3
1/3-y=-1
Y=-2/3
F)x-2y=-8 |x2
2x-4y=-16
2x-4y=-16
3x+4y=-4
Adunam
5x=-20
X=-20/5
X=-4
4-2y=-8
2y=12
Y=6
Sper ca te-am ajutat!
[tex]\it f)\ \ \begin{cases} \it x-2y=-8\ \Rightarrow\ x=2y-8\ \ \ \ \ (*)\ \ rela\c{\it t}ia\ de\ substitu\c{\it t}ie\\ \\ \it 3x+4y=-4\end{cases}\\ \\ \it 3x+4y=-4\ \stackrel{(*)}{\Longrightarrow}\ 3(2y-8)+4y=-4\ \Rightarrow\ 6y-24+4y=-4\ \Rightarrow\\ \\ \ \Rightarrow\ 6y+4y=24-4\ \Rightarrow\ 10y=20|_{:{10}}\ \Rightarrow\ y=2\\ \\ y=2\ \stackrel{(*)}{\Longrightarrow}\ x=2\cdot2-8=4-8=-4\\ \\ S=\{-4,\ 2\}[/tex]